RECRUITMENT SYSTEM MAHASANTRI MA’HAD ALY DARUSSALAM BLOKAGUNG TEGALSARI BANYUWANGI - Zainal Abidin; M. Himami Baydarus (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
This research is directed at 2 main points, namely: (1) How is the mahasantri recruitment system at the Ma’had Aly institution. (2) what factors hinder and support the mahasantri recruitment system at the institution. This study uses qualitative methods as for the reasons for the research using qualitative methods because in this study, the researcher is at the same time an instrument in collecting data on the mahasantri recruitment system, so that researchers have a very large method, because what happens during the research needs further elaboration in writing a report from the data obtained and the analysis conducted, it can be concluded that: (1) Mahasantri recruitment system through selection, turats polar tests held by the institution, this is what distinguishes it from other tertiary institutions. (2) The inhibiting and supporting factors in the recruitment of mahasantri is the difficulty in finding a mahasantri who is competent in terms of tafaqquh fiddin and able to read and understand polar text, while the supporting factor is the priority in this institution is the quality of student outcomes